Penggunaan Kontrasepsi Darurat Berdasarkan Permenkes No. 97 Tahun 2014 Perspektif Maqāṣid al-Syarī’ah - Herdiansa Herdiansa (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
The use of contraception is one of the steps used by the Indonesian Government to support the “Kelurga Berencana” (KB) program. The various types of contraception regulated according to the Permenkes No. 97 of 2014 is emergency contraception, that can be used with the aim of preventing unwanted pregnancy and is used after sexual intercourse. The research aims to be an strengthens of previous research with the same discussion. However, in this research the authors used a different analytical tools to analyze this by using the theory of maqāṣid al-syarī'ah. The type of research is the library research method with the data collection process referring to primary, secondary data sources and also other supporting sources in this research. This research uses a normative juridical approach, an approach that seeks the truth of a matter, including legal concepts and principles from all sources of something (cases, laws or regulations). The results of this research are emergency contraception (KONDAR). If analyzed from the concept of maqāṣid al-syarī'ah, it can be concluded that the use of KONDAR is a functions as an effort to prevent the birth of children who do not have a clear lineage status because their mothers are victims of sexual violence. In terms of saving life and lineage, the use of KONDAR is a form of the main benefit of hifz al-nasf and the main benefit of hifz al-nasl.